Frequencies : international spectrum policy - Taylor, Gregory, 1967-; Middleton, Catherine, 1963- (McGill-Queen's University Press, 2020)
"Our digital world is increasingly mobile. All mobile communication rests upon access to one invisible, essential element: the radio spectrum. In Frequencies, Gregory Taylor and Catherine Middleton bring together diverse national perspectives to explore the current and future state of spectrum governance worldwide. Spectrum is a foundational component of our contemporary communication infrastructure. The stakes are massive: mobile network operators have invested billions via national spectrum auctions to claim exclusive use of prime spectrum bands. Despite this windfall for national governments, many people around the globe remain disconnected from mobile service, yet international policy comparisons that can help us understand these disparities and differences are rare. Frequencies offers illuminating case studies from around the world, including Finland, Mexico, New Zealand, India, and Canada, as well as forward-thinking approaches to our use of radio frequencies that encourage greater public benefit and technological advancement. The contributors to Frequencies represent a wide array of disciplinary backgrounds, united by the common goal of maximizing the value and access to the public good that is the radio spectrum. Spectrum policy affects everyone, whether listening to the radio, making an emergency phone call, or scrolling through social media updates. Frequencies seeks to broaden the discussion about our management of this primary resource necessary for how the world shares information."-- Provided by publisher
Keywords: Telecommunication policy.; Telecommunication -- International cooperation.; Radio resource management (Wireless communications); Radio frequency allocation -- Government policy.; Wireless communication systems -- Government policy.; Broadband communication systems -- Government policy.; Télécommunications -- Politique gouvernementale.; Télécommunications -- Coopération internationale.; Ressources radio -- Gestion.; Radiofréquences -- Attribution -- Politique gouvernementale.; Transmission sans fil -- Politique gouvernementale.; Systèmes de télécommunications à large bande -- Politique gouvernementale.; POLITICAL SCIENCE -- Public Policy -- Communication Policy.; Broadband communication systems -- Government policy; Radio frequency allocation -- Government policy; Telecommunication -- International cooperation; Telecommunication policy; Wireless communication systems -- Government policy